2019
DOI: 10.3390/rs11020139
|View full text |Cite
|
Sign up to set email alerts
|

Walker: Continuous and Precise Navigation by Fusing GNSS and MEMS in Smartphone Chipsets for Pedestrians

Abstract: The continual miniaturization of mass-market sensors built in mobile intelligent terminals has inspired the development of accurate and continuous navigation solution for portable devices. With the release of Global Navigation Satellite System (GNSS) observations from the Android Nougat system, smartphones can provide pseudorange, Doppler, and carrier phase observations of GNSS. However, it is still a challenge to achieve the seamless positioning of consumer applications, especially in environments where GNSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In Zhang et al (2018), the quality of the raw Global Positioning System (GPS) measurements from a Google Nexus 9 tablet was analyzed by comparing the C/N 0 and single-differenced code residuals with the corresponding measurements from geodetic-grade receivers, and the pseudorange rate, phase rate, and Doppler data from the smart device were also examined for the purpose of deriving velocity. The similar analyses about the data quality of the raw GNSS measurements from smartphones can also be found in Lu et al (2018) and Zhu et al (2019). Håkansson (2019) further assessed the multipath effect of GNSS observations with smart devices on positioning performance.…”
Section: Introductionmentioning
confidence: 72%
“…In Zhang et al (2018), the quality of the raw Global Positioning System (GPS) measurements from a Google Nexus 9 tablet was analyzed by comparing the C/N 0 and single-differenced code residuals with the corresponding measurements from geodetic-grade receivers, and the pseudorange rate, phase rate, and Doppler data from the smart device were also examined for the purpose of deriving velocity. The similar analyses about the data quality of the raw GNSS measurements from smartphones can also be found in Lu et al (2018) and Zhu et al (2019). Håkansson (2019) further assessed the multipath effect of GNSS observations with smart devices on positioning performance.…”
Section: Introductionmentioning
confidence: 72%
“…It indicates that the modified paired overbound method has stronger robustness to “large deviations”, with a probability of more than 70%. Besides SBAS, the MPO method proposed in this article can also be used in other conservative error modeling fields related to integrity [39,40,41]. However, it is important to note that the MPO method is only suitable for scenarios that have a linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, work has shown that the use of phase measurements by time difference can be more effective and provide a very accurate velocity estimate (Pierluigi, Antonio, Salvatore, & Salvatore, 2015). Thus, TDCP can be used to correct INS measurements and errors or in a PDR approach to correct walking direction estimation error but also the step-length error (Angrisano, Vultaggio, Gaglione, & Crocetto, 2019;Feng et al, 2019;Tao, Zhang, Zhu, Wang, & Teng, 2018).…”
Section: State Of the Artmentioning
confidence: 99%